Association of Filifactor alocis and its RTX toxin gene ftxA with periodontal attachment loss, and in synergy with Aggregatibacter actinomycetemcomitans - Razooqi, Zeinab; Tjellström, Ingeborg; Höglund Åberg, Carola; Kwamin, Francis; Claesson, Rolf; Haubek, Dorte; Johansson, Anders; Oscarsson, Jan (Frontiers in Cellular and Infection Microbiology, 2024)
Abstract The Gram-positive bacterium, Filifactor alocis is an oral pathogen, and approximately 50% of known strains encode a recently identified repeat-in-toxin (RTX) protein, FtxA. By assessing a longitudinal Ghanaian study population of adolescents (10-19 years of age; mean age 13.2 years), we recently discovered a possible correlation between deep periodontal pockets measured at the two-year follow-up, presence of the ftxA gene, and a high quantity of F. alocis. To further understand the contribution of F. alocis and FtxA in periodontal disease, we used qPCR in the present study to assess the carriage loads of F. alocis and the prevalence of its ftxA gene in subgingival plaque specimens, sampled at baseline from the Ghanaian cohort (n=500). Comparing these results with the recorded clinical attachment loss (CAL) longitudinal progression data from the two-year follow up, we concluded that carriers of ftxA-positive F. alocis typically exhibited higher loads of the bacterium. Moreover, high carriage loads of F. alocis and concomitant presence of the ftxA gene were two factors that were both associated with an enhanced prevalence of CAL progression. Interestingly, CAL progression appeared to be further promoted upon the simultaneous presence of F. alocis and the non-JP2 genotype of Aggregatibacter actinomycetemcomitans. Taken together, our present findings are consistent with the notion that F. alocis and its ftxA gene promotes CAL during periodontal disease.